2003
DOI: 10.1038/sj.onc.1206542
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of metastasis suppressor gene product KiSS-1 protein/metastin by matrix metalloproteinases

Abstract: A human placenta cDNA library was screened by the expression cloning method for gene products that interact with matrix metalloproteinases (MMPs), and we isolated a cDNA whose product formed a stable complex with pro-MMP-2 and pro-MMP-9. The cDNA encoded the metastasis suppressor gene KiSS-1. KiSS-1 protein was shown to form a complex with pro-MMP. KiSS-1 protein is known to be processed to peptide ligand of a G-proteincoupled receptor (hOT7T175) named metastin, and suppresses metastasis of tumors expressing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
112
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 31 publications
5
112
0
8
Order By: Relevance
“…27 KISS1 is able to diminish MMP9 expression by reducing nuclear factorkB binding to its promoter, 28 and it has been suggested that MMPs may serve as negative regulators of KISS1. 29 Our findings that demonstrate an inverse relationship between KISS1 expression and prognosis support the concept that KISS1 and MMP9 may somehow be related.…”
Section: Discussionsupporting
confidence: 81%
“…27 KISS1 is able to diminish MMP9 expression by reducing nuclear factorkB binding to its promoter, 28 and it has been suggested that MMPs may serve as negative regulators of KISS1. 29 Our findings that demonstrate an inverse relationship between KISS1 expression and prognosis support the concept that KISS1 and MMP9 may somehow be related.…”
Section: Discussionsupporting
confidence: 81%
“…Interleukin receptor IL-2Rα no yes (Sheu et al, 2001) KiSS-1 protein/metastin yes yes (Takino et al, 2003) Kit-ligand yes (Heissig et al, 2002) Monocyte chemoattractant protein MCP-3 yes no (McQuibban et al, 2002) Monokine induced by interferon IFN-γ (MIG/CXCL -9) yes (Van den Myelin basic protein yes yes (Chandler et al, 1995) Myosin heavy chain yes yes (Rouet-Benzineb et al, 1999) Plasminogen yes yes (O'Reilly et al, 1999;Patterson and Sang, 1997) Platelet factor (PF)-4 yes…”
Section: (Van Den Steen Et Al 2003)mentioning
confidence: 99%
“…8 Cleavage of the KP 45−54 peptide between residues 51 and 52 by matrix metalloproteinases abolishes the activation of GPR-54 by the KP 45−54 peptide. 9 The KP 42−54 and KP 45−54 peptides also activate NPFF receptors, 10,11 and some of the actions of KP peptides could be mediated by NPFF receptor activation.There are profound changes in KP signaling at menopause 12 and notable sex differences in hypothalamic neurodegeneration in the elderly. 13 This correlates with a marked elevation of KP peptides in the hypothalamus of postmenopausal women that is not seen in males.…”
mentioning
confidence: 99%
“…9 The neuroprotective actions of the KP receptor antagonist P234 are additive to the protection observed with KP 42−54 and KP 45−50 and suggest that the neuroprotective mechanism is more complex. Since the P234 peptide is a derivative of KP 45−54 with modifications at residues 1, 5, and 8 and binds the KP receptor, it is possible that it has receptor activity as a partial agonist that is key to the neuroprotection observed but not to GnRH release.…”
mentioning
confidence: 99%